PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI KOMUNIKASI PEMASARAN MODERN PADA BRAND NASI UDUK IBU SUN - EKA WARDANA, ANDRI; FARID, M.MIFTAH (Lentera Jurnal Pengabdian Masyarakat, 2024)
This research was conducted to find out the motives of the use of instagram by the brand restaurnt Sun's mother's rice by using the theory uses and gratificatons. According to Mquail and colleagues (1972) one of the theories of mass communication, namely the Theory of Uses & Gratification, is that of Diversion Personal Relationships, Personal Identity and Surveillance. This research uses qualitative methods with descriptive methods of research with data collection research techniques through observations and interviews on 4 sources that are people that are spanning within the scope of the rice restaurant mother sun. The results of the research showed that the brand was successful in marketing through social media instagram with the motive of media use by users. The redirection motives are already appropriate in building relationships with customers and can also strengthen relationships and increase engagement with audiences. Personal relationship motives emphasize the importance of active and responsive interaction with customers on social media platforms to build strong relationships and increase engagement as well as purchasing intensity. Social identity motives Strategic approaches to personal branding in digital content are essential to differentiate in the market, build customer loyalty, and create strong and lasting relationships with customers. The Platform not only helps in introducing new products and up-to-date information, but also in building a strong and loyal community among their customers, raising brand awareness, and maximizing dedicated promotions.